High-alkaline water-splitting activity of mesoporous 3D heterostructures: an amorphous-shell@crystalline-core nano-assembly of Co-Ni-phosphate ultrathin-nanosheets and V- doped cobalt-nitride nanowires - Singh, Thangjam Ibomcha; Maibam, Ashakiran; Cha, Dun Chan; Yoo, Sunghoon; BabaRao, Ravichandar; Lee, Sang Uck; Lee, Seunghyun (Advanced Science, 2022)
Introducing amorphous and ultrathin nanosheets of transition bimetal phosphate arrays that are highly active in the oxygen evolution reaction (OER) as shells over an electronically modulated crystalline core with low hydrogen absorption energy for an excellent hydrogen evolution reaction (HER) can boost the sluggish kinetics of the OER and HER in alkaline electrolytes. Therefore, in this study, ultrathin and amorphous cobalt-nickel-phosphate (CoNiPOx) nanosheet arrays are deposited over vanadium (V)-doped cobalt-nitride (V-3%-Co4N) crystalline core nanowires to obtain amorphous-shell@crystalline-core mesoporous 3D-heterostructures (CoNiPOx@V-Co4N/NF) as bifunctional electrocatalysts. The optimized electrocatalyst shows extremely low HER and OER overpotentials of 53 and 270 mV at 10 mA cm(-2), respectively. The CoNiPOx@V-3%-Co4N/NF (+/-) electrolyzer utilizing the electrocatalyst as both anode and cathode demonstrates remarkable overall water-splitting activity, requiring a cell potential of only 1.52 V at 10 mA cm(-2), 30 mV lower than that of the RuO2/NF (+)/20%-Pt/C/NF (-) electrolyzer. Such impressive bifunctional activities can be attributed to abundant active sites, adjusted electronic structure, lower charge-transfer resistance, enhanced electrochemically active surface area (ECSA), and surface- and volume-confined electrocatalysis resulting from the synergistic effects of the crystalline V-3%-Co4N core and amorphous CoNiPOx shells boosting water splitting in alkaline media.
Keywords: core-shell; hydrogen productions; metal nitrides; metal phosphates; synergistic effect; water-splitting

Critical review on amorphous-crystalline heterostructured electrocatalysts for efficient water splitting - Singh, Manjinder; Cha, Dun Chan; Singh, Thangjam Ibomcha; Maibam, Ashakiran; Paudel, Dasu Ram; Nam, Dong Hwan; Kim, Tae Hyeong; Yoo, Sunghoon; Lee, Seunghyun (Materials Chemistry Frontiers, 2023)
Introducing complementary active materials in tandem as heterostructures of various shapes and sizes can significantly improve the physicochemical properties of the developed materials. Recently, the use of amorphous materials in conjunction with crystalline moieties as highly efficient electrocatalysts for water-splitting electrolyzers has surged rapidly. Excellent bifunctional activity for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) can be achieved from amorphous-crystalline-based materials owing to their remarkably conductive crystalline phase as well as their long-range disordered amorphous phase. In addition, the high specific surface area, disordered structure, and enhanced structural stability can accommodate various defects and strains that develop during in situ electrochemical reactions. Consequently, amorphous materials can be used as both surface-confined and volume-confined electrocatalysts. Although crystalline materials have better electronic properties as well as higher thermal and mechanical stability, they suffer from limited activity due to only surface-confined electrocatalysis. In this regard, the judicious integration of crystalline and amorphous active materials suitable for the OER and HER can tremendously enhance their bifunctional electrocatalytic activities owing to their synergistic effects. The variety in the choice of amorphous and crystalline counterparts presents ample opportunities for further exploration of the development of amorphous-crystalline heterostructured materials with unique properties. However, considering the recent massive developments in the understanding and protocols for fabricating such heterostructures, a critical review is vital for further advancement in this direction. Although some review papers have focused only on amorphous materials, including their synthesis methods, properties, and applications, no critical review that provides an overview emphasizing amorphous-crystalline heterostructures for electrocatalytic water-splitting applications has been published. In this regard, this review aims to present comprehensive details on the recent developments in the fabrication of different amorphous-crystalline heterostructures, the choice of the composition of each component, and the resulting physicochemical properties for the OER, HER, and overall water-splitting. It provides an in-depth understanding of amorphous-crystalline material synthesis protocols, their selection rationale, and their targeted physicochemical properties. This review also provides thought-provoking ideas and long-term perspectives for future research. This review presents comprehensive details on recent developments in the fabrication of different amorphous-crystalline heterostructures, their compositions, and the resulting physicochemical properties for OER, HER, and overall water splitting.

Metal-organic framework-derived mesoporous B-doped CoO/Co@N-doped carbon hybrid 3D heterostructured interfaces with modulated cobalt oxidation states for alkaline water splitting - Cha, Dun Chan; Singh, Thangjam Ibomcha; Maibam, Ashakiran; Kim, Tae Hyeong; Nam, Dong Hwan; BabaRao, Ravichandar; Lee, Seunghyun (Small, 2023)
Heteroatom-doped transition metal-oxides of high oxygen evolution reaction (OER) activities interfaced with metals of low hydrogen adsorption energy barrier for efficient hydrogen evolution reaction (HER) when uniformly embedded in a conductive nitrogen-doped carbon (NC) matrix, can mitigate the low-conductivity and high-agglomeration of metal-nanoparticles in carbon matrix and enhances their bifunctional activities. Thus, a 3D mesoporous heterostructure of boron (B)-doped cobalt-oxide/cobalt-metal nanohybrids embedded in NC and grown on a Ni foam substrate (B-CoO/Co@NC/NF) is developed as a binder-free bifunctional electrocatalyst for alkaline water-splitting via a post-synthetic modification of the metal-organic framework and subsequent annealing in different Ar/H-2 gas ratios. B-CoO/Co@NC/NF prepared using 10% H-2 gas (B-CoO/Co@NC/NF [10% H-2]) shows the lowest HER overpotential (196 mV) and B-CoO/Co@NC/NF (Ar), developed in Ar, shows an OER overpotential of 307 mV at 10 mA cm(-2) with excellent long-term durability for 100 h. The best anode and cathode electrocatalyst-based electrolyzer (B-CoO/Co@NC/NF (Ar)(+)//B-CoO/Co@NC/NF (10% H-2)(-)) generates a current density of 10 mA cm(-2) with only 1.62 V with long-term stability. Further, density functional theory investigations demonstrate the effect of B-doping on electronic structure and reaction mechanism of the electrocatalysts for optimal interaction with reaction intermediates for efficient alkaline water-splitting which corroborates the experimental results.
Keywords: 3D heterostructures; B-doped metal-oxides; electrocatalysts; hydrogen evolution reactions; metal-organic frameworks; oxygen evolution reactions